Efektivitas Formasi Tempat Duduk Tipe U dan Chevron Terhadap Hasil Belajar Peserta Didik - Meta Khoirotunnisa; Arwin Achmad; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2018)
This study aimed to determine the effectiveness of seating formation U shape and Chevron types towards student learning outcomes on structure and function of animal tissues subject in Islamic Senior High School 1 Bandar Lampung. The research design was pretest-posttest non-equivalent groups. The population was XI grade science students and samples were XI science 1, XI science 2, and XI science 3 grade’s students which were selected by purposive sampling technique. This research data were the result of students learning were obtained through pretest-posttest, students’ self assessment affective aspects and students’ psychomotor aspect observation sheets. Cognitive aspects of learning outcome data were analyzed by One-Way Anova test and by Independent Sample t-test. The data of affective and psychomotor aspects were analyzed using Qualitative Achievement Index and calculated score improvement. The result showed that the experiment class XI Science 2 had the highest cognitives N-gain and score improvement each aspects. Therefore, there were differences of effectiveness of three seating formations that applied towards student learning outcomes on structure and function of animal tissues subject.Penelitian ini bertujuan mengetahui efektivitas formasi tempat duduk tipe U dan Chevron terhadap hasil belajar peserta didik pada materi pokok struktur dan fungsi jaringan hewan di MAN 1 Bandar Lampung. Desain penelitian ini adalah pretest-postest non ekuivalen. Populasi penelitian ini adalah seluruh peserta didik kelas XI MIA dan sampelnya adalah peserta didik kelas XI MIA 1, XI MIA 2, dan XI MIA 3 yang diambil dengan teknik purposive sampling. Data hasil penelitian berupa hasil belajar peserta didik yang diperoleh melalui pretest-postest, lembar penilaian diri afektif dan lembar pengamatan psikomotorik. Data aspek kognitif dianalisis dengan uji One-Way Anova  dan uji t. Data aspek afektif dan psikomotorik dianalisis menggunakan Indeks Prestasi Kualitatif serta dihitung peningkatan nilainya. Hasilnya menunjukkan bahwa peserta didik kelas eksperimen XI MIA 2 memiliki N-gain kognitif dan peningkatan nilai aspek afektif dan psikomotorik tertinggi daripada peserta didik kelas eksperimen lainnya. Oleh karena itu, terdapat  perbedaan efektivitas dari ketiga formasi tempat duduk yang diterapkan terhadap hasil belajar peserta didik pada materi pokok struktur dan fungsi jaringan hewan.Kata kunci : efektivitas, formasi tempat duduk, hasil belajar, jaringan hewan